2012
DOI: 10.1002/ijc.27779
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of fluorine 18 fluorodeoxyglucose positron emission tomography/computed tomography for the detection of metastases in non–small‐cell lung cancer patients

Abstract: In the recent years, fluorine 18 fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET)/computed tomography (CT) has emerged as a new modality for staging non-small-cell lung cancer (NSCLC) patients. The aim of this meta-analysis was to assess the diagnostic value of 18 F-FDG PET/CT in detecting metastatic lesions in NSCLC patients. Meta-analysis methods were used to pool sensitivity, specificity, positive and negative likehood ratios, diagnostic odd ratios and to construct a summary receiver-operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 71 publications
3
70
0
4
Order By: Relevance
“…With tracer accumulation 18 F-FDG PET visualizes regions of enhanced metabolic activity and complements other imaging modalities based on structural anatomic changes (Wu et al, 2013). 18 F-FDG PET had a better performance in esophagus, thyroid, nasopharyngeal and lung carcinoma (Kato et al, 2005;Shinji et al, 2007;Liu et al, 2010;Chang et al, 2013) when compared with the isotope BS.…”
Section: Introductionmentioning
confidence: 99%
“…With tracer accumulation 18 F-FDG PET visualizes regions of enhanced metabolic activity and complements other imaging modalities based on structural anatomic changes (Wu et al, 2013). 18 F-FDG PET had a better performance in esophagus, thyroid, nasopharyngeal and lung carcinoma (Kato et al, 2005;Shinji et al, 2007;Liu et al, 2010;Chang et al, 2013) when compared with the isotope BS.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed no difference in time to progression and OS between younger and elder patients (>70years) 12,13 . Others obtained a higher risk of death in patients aged 65 and older ones 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis including 13 studies and 2873 patients, sensitivity and specificity of PET-CT in the detection of extrathoracic metastases were estimated respectively to 77 and 95% (18). These numbers include the detection of brain metastases, were there is a known lack of sensitivity du to the high physiological uptake of FDG in the cerebral cortex.…”
Section: Global Sensitivity and Specificitymentioning
confidence: 99%
“…PET imaging is based on positron-emitters such as 18 F, 15 O or 82 Rb, among others. The annihilation of the positron emitted leads to the emission of two 180°-sided 511 kev photons, detected by a full crystal ring (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation